Designing an Intuitive UI/UX for Laundry and Household Cleaning Services Using a User-Centered Design Thinking Approach - George Morris William Tangka; Joe Yuan Mambu; Edson Yahuda Putra (Journal of Information System Research (JOSH), 2025)
The growing demand for footwear and accessory care reflects an increasing awareness of cleanliness and personal appearance. This study focuses on a cleaning service business specializing in shoes, bags, and strollers, with shoes as the primary focus. Operational challenges, including inefficient customer communication and delays due to high demand, impact customer satisfaction. Using the Design Thinking method, this research develops a user-centered User Interface (UI) and User Experience (UX) for the business's application. The Design Thinking process—empathize, define, ideate, prototype, and test—helped identify pain points and generate tailored solutions, such as improved navigation and task flow. Usability testing involved 18 participants performing key tasks, including booking services and tracking orders, with success rates and error metrics as evaluation criteria. The testing yielded a 70.6% task completion success rate, indicating improved service efficiency. However, the 54.4% misclick rate, higher than typical benchmarks for similar applications (30–40%), highlights significant navigation challenges. Future iterations will focus on refining the interface layout and enhancing task clarity to reduce errors and improve usability. These findings emphasize the value of iterative, user-centered design in addressing operational inefficiencies and enhancing the customer experience.